Respuestas

2012-06-12T00:10:59+02:00

A - B        A    =  5i - 9 j

               -B    = -6i + 10j

               --------------------

                R =  -i + j

 

A + B         A = 5i  - 9j

                 B = 6i -10j

                ----------------

 

                  R = 11i - 19j                   tang R = Ry/RX     

                                                       tang R = - 19/ 11

 

                                                               R = - 59,93

                                                               R = 360 - 59,93 =  300,07